Assessment of the feed additive consisting of ammonium chloride (Amoklor™) for all ruminants, dogs and cats for the renewal of its authorisation and its extension of use to sows (Latochema Co Ltd). (11th January 2023) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for the renewal of authorisation of ammonium chloride (Amoklor™) as a zootechnical additive for all ruminants, dogs and cats and its extension of use in sows for urinary health. The applicant provided evidence that the additive currently in the market complies with the existing conditions of authorisation. There is no new evidence that would lead the FEEDAP Panel to reconsider its previous conclusions. Thus, the Panel concludes that the additive remains safe for ruminants other than lambs for fattening, lambs for fattening, cats and dogs, consumers and the environment under the current authorised conditions of use. Inhalation exposure of the additive is considered very likely. Amoklor™ should be considered a potential respiratory sensitiser but not a skin sensitiser. The additive is not irritant to the skin, but the Panel could not conclude on its eye irritation potential. The present application for renewal of the authorisation does not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive. Therefore, there was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation. Regarding the extension of use in sows, the FEEDAP Panel concludes that the additive is safe and efficacious for sows at the inclusion level of 5, 000 mg/kg feedingstuffs from week 9th to 11th of gestation and from week 15th of gestation to 1st of lactation.